The Effect of Employee Engagement and Work Discipline on Employee Performance at the National Land Agency Office of Langkat Regency - Zuraida Khair; M. Chaerul Rizky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine how much work discipline and employee engagement impact employee performance at the National Land Agency Office in Langkat Regency. The research methodology is associative and quantitative. A complete sampling technique was used to select 73 employees from the entire population. A questionnaire created using the indicators of each variable was used to gather primary data. Multiple linear regression techniques were used in data analysis, utilizing SPSS version 25 software to examine the influence concurrently and partially. The findings demonstrated that, partially and simultaneously, work discipline and employee engagement both significantly and favorably affect employee performance. This result emphasizes how crucial staff discipline and engagement are to raising the efficacy of government agency performance.